Analisis vegetasi tumbuhan angiospermae di desa ranga-ranga kecamatan masama kabupaten banggai - Nurlia; Wahyudin Abd. Karim (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
The structure and composition of vegetation are influenced by different types of plants, sovegetation constituent data is needed to determine the diversity of plant species. The purposeof this study was to determine the structure and composition of Angiosperms plant vegetationconstituents in Ranga-ranga Village. The research method used was experimental with a typeof exploratory descriptive research using a plot line method of 20 plots. The researchinstrument was an observation sheet. Research data namely the type and number of plants.Quantitative descriptive data analysis techniques to obtain the value of relative frequency,relative density, relative dominance, and index of important values. The results showed thatthe highest relative frequency of A. occidentale (FR = 31.03%), the lowest was R. communis,M. sago, A. carambola, T. cacao, M. indica, A. heterophyllus, S. lineatum, C. pulcherrima,and M. calabura (FR = 1.29%). The highest relative density of C. rotundus (KR = 31.39%),the lowest C. pulcherima and C. Arabica (KR = 0.89%). The highest relative dominance of T.grandis (DR = 16.15%), the lowest M. indica (DR = 4.67%). The highest importance index isA. occidentale (INP = 59.85%), the lowest is R. communis, A. carambola, M. indica, A.heterophyllus, C. pulcherrima, and M. calabura (INP = 2.33%). The conclusion of theresearch is the structure and composition of Angiosperms plants vegetation in Ranga-rangaVillage, varying at the level of trees, poles, saplings, and seedlings